Comparative Analysis of the Trajectories of ProjectilesFired from Polish Small Arms Systems:MSBS-5.56 and BERYL - Łukasz SZMIT (Analiza porównawcza torów pocisków wystrzelonych z karabinków systemu MSBS-5,56 i wz. 1996, 2021)
This paper presents the results of the theoretical external ballistic calculations for projectiles fired from barrels which correspond to the barrels used in two Polish small arms systems: MSBS-5.56 system (MSBS GROT standard rifle and MSBS GROT carbine) and BERYL system (BERYL standard rifle and MINI BERYL carbine). The results obtained allowed the analyse of the effects of barrel length and the associated initial projectile velocity on the nature of projectile trajectory, particularly the over height and projectile range obtained along the trajectories. The analysis of the results facilitated an assessment of the scope of proposed changes in the settings of the firearm sights, resulting from the use of barrels of different lengths and the consequential changes in projectile trajectory.
Keywords: Balistyka zewnętrzna pocisków małokalibrowych